Synthesis of Substituted Pyrrolo[2,1-a]isoquinolines by Gold-Catalyzed Domino Cyclization of Alkynyl Iminoesters - Sugimoto, Kenji; Hoshiba, Yuya; Tsuge, Kiyoshi; Matsuya, Yuji (Synthesis, 2016)
A novel gold-catalyzed double cyclization leading to a biologically important pyrroloisoquinoline skeleton was established. The reaction sequence involving 6-exo-dig cyclization of alkynyl iminoester and [3+2] cycloaddition of azomethine ylide proceeded smoothly in the presence of 0.5–1.0 mol% (CyJohnPhos)AuCl/AgOTf at 65 or 80 °C. This strategy with (–)-phenylmenthol-derived iminoester enables a generation of chiral azomethine ylide in situ to construct an optically active pyrroloisoquinoline in a highly diastereoselective manner. An alkyne and alkenes with electron-withdrawing group could be utilized as dipolarophiles. Iminoesters having terminal and internal alkynes were applied as reaction substrates to afford the corresponding pyrroloisoquinolines.
Keywords: domino reaction; cycloaddition; gold; azomethine ylides; pyrroloisoquinolines